KARAKTERISTIK BATUGAMPING FORMASI MARUNI DAERAH WARMARE DAN SEKITARNYA KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Yorana Tabuni; Hermina Haluk; Nur Alzair (INTAN Jurnal Penelitian Tambang, 2021)
This study aims to determine the characteristics of the Maruni Formation limestones in the Warmare area and its surroundings in Manokwari Regency by using geological mapping, and petrographic and paleontological analysis. Based on physical, petrographic and paleontological characteristics, the limestone facies in the study area consist of packstone, wackestone, mudstone and crystalline. Limestone diagenetic processes that occur in the study area are cementation diagenesis and neomorphism. Limestone depositional environment consists of two depositional environments. First, the depositional environment is in a shallow ocean shelf with limited circulation (SMF10: bioclastic packstone/wackestone with worm skeletal grains and SMF18: Grainstone or packstone with abundant foraminifera or algae; FZ7-FZ8; Platform Interior – Openmarine, Restricted). After that, sea ​​level conditions decreased, so that the depositional environment shifted towards the sea (SMF2: Micobioclastic peloidal calcisiltite and SMF3: Pelagic mudstone/wackstone – FZ3: Toe of Slope). However, in the complex classification of facies, the research area is included in the lagoon depositional environment.